Linking individuals with ecosystems: Experimentally identifying the relevant organizational scale for predicting trophic abundances - Ovadia, Ofer (The National Academy of Sciences, 2002)
Ecosystems are complex owing to the fact that emergent properties like trophic structure and productivity depend on details related to lower-scale interactions among individuals. A key challenge is identifying how much individual-level detail is needed to predict patterns at the ecosystem level. We tested for the effect of individual herbivore body size on trophic interactions and consequent abundances of plant and herbivore trophic levels in a New England meadow ecosystem. Body size is an important determinant of vulnerability to predation and thus should influence the way individuals tradeoff time spent foraging against time spent avoiding contact with predators. Such tradeoffs can then influence the degree of damage herbivores inflict on their plant resources. We experimentally assigned field-caught grasshoppers to three distinct body size treatment groups (small, normal, and large) and crossed them with two spider predator treatments (spider present and absent) in a fully replicated design. We observed size-dependent differences in grasshopper survival and development. Moreover, predators caused grasshoppers to inflict greater damage to herbs and lesser damage to grasses relative to treatments without predators. However, there were no size-dependent differences in net damage level on grasses and herbs in either predator or no predator treatments owing to size-dependent compensation in grasshopper foraging effort. We thus conclude that in this ecosystem the foraging-predation risk tradeoff displayed by typical or average-sized herbivore is a sufficient amount of individual-level detail needed to explain ecosystem patterns.